1990
DOI: 10.1002/1097-0142(19900601)65:11<2426::aid-cncr2820651104>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with mitomycin, vindesine, and cisplatin for non-small cell lung cancer association of antitumor activity with initial tumor burden and treatment center

Abstract: From 1984 through 1986, 205 patients with non-small cell lung cancer were entered into a group-wide trial of the Swiss Group for Clinical Cancer Research (SAKK). This trial evaluated the combination of mitomycin (8 mg/m2 intravenously [IV] on day 1), vindesine (3 mg/m2 IV on days 1 and 8), and cisplatin (60 mg/m2 IV on day 1) with forced diuresis, repeated every 4 weeks (MiViP regimen). One hundred eighty-three patients were evaluable. Six complete and 69 partial responses were documented for an overall respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In four reports of the two drug combination of MMC + vindesine the effect of prior chemotherapy was evident since 42/84 (48%) of patients without prior therapy responded compared with 6/53 (11%) with prior therapy (179,180,181,182). A survey of 17 studies of MVP with vindesine (references [183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199] gave an overall response of 459/1290 (36%). The same trends were observed regarding cisplatin dose and prior chemotherapy as seen with vinblastine, but the significance was less marked.…”
Section: Non-small-cell Lung Cancer (Nsclc)mentioning
confidence: 99%
“…In four reports of the two drug combination of MMC + vindesine the effect of prior chemotherapy was evident since 42/84 (48%) of patients without prior therapy responded compared with 6/53 (11%) with prior therapy (179,180,181,182). A survey of 17 studies of MVP with vindesine (references [183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199] gave an overall response of 459/1290 (36%). The same trends were observed regarding cisplatin dose and prior chemotherapy as seen with vinblastine, but the significance was less marked.…”
Section: Non-small-cell Lung Cancer (Nsclc)mentioning
confidence: 99%
“…The number of metastatic sites may represent the ability of the tumour cells to spread to other locations and, thus, to its aggressiveness, leading to treatment resistance [63]. Similarly, more metastatic sites have been associated with circulating tumour cells heterogenicity, which may hinder antitumor response to systemic therapies and reduce survival [64][65][66][67][68]. Specifically, among NSCLC patients treated with ICP, a study accessing the prognostic value of metastatic sites reported a worse PFS in patients with more than one metastatic site [50].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a prospective study by Sanchez et al reported that the numbers of metastatic sites and lesions had prognostic relevance [ 17 ]. Tumor burden has exhibited prognostic relevance for survival irrespective of therapeutic agents, cytotoxic chemotherapy, and use of a tyrosine kinase inhibitor such as gefitinib [ 18 20 ]. Zhao et al, reported that cancer cells can tolerate chemotherapy and acquire more stemness under hypoxic conditions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%